Lamellar melting, not crystal motion, results in softening of polyoxymethylene on heating - Kumaraswamy, Guruswamy; Surve, Nikita S.; Mathew, Renny; Rana, Abhimanyu; Jha, Saroj K.; Bulakh, Neelima N.; Nisal, Anuya; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Ratnagiri, Ram (Macromolecules, 2012)
We probe temperature-dependent changes in the semicrystalline microstructure of polyoxymethylene using a combination of modulated DSC, SAXS, and solid-state NMR to characterize macroscopic behavior, lamellar-level structure, and molecular environments, respectively, and correlate these with the change in mechanical properties probed using DMA and AFM. Two model samples are investigated: a melt crystallized sample prepared by injection molding and a sample obtained by crystallization from dilute solution. Our investigations reveal that, for both samples, there is an increase in crystalline motions and in the amorphous content on heating. DMA and AFM measurements reveal that the modulus of the molded sample decreases on heating to about 100 degrees C; however, there is a significant difference in behavior of the solution crystals, where we observe no significant decrease in stiffness (from AFM measurements). Thus, in contrast to previous reports, we demonstrate that the decrease in modulus on heating polyoxymethylene does not correlate with chain motions in the crystalline regions. We use SAXS to probe the semicrystalline morphology for the samples on heating and show that, for the molded sample, there is a distribution of lamellar thickness at room temperature and that the thin lamellae in this distribution melt on heating. In contrast to the behavior of the melt crystallized samples, the solution crystals exhibit no change in the lamellar stacking on heating to 150 degrees C. We also demonstrate that, on heating, the amorphous regions in the solution crystals always appear to have restricted mobility while there are mobile and low mobility amorphous regions in the molded samples. Our results suggest that, contrary to conventional belief, the decrease in modulus on heating polyoxymethylene arises not from motions in the crystalline lamellae but primarily from melting of thin lamellae.

L-Proline functionalized dicationic framework of bifunctional mesoporous organosilica for the simultaneous removal of lead and nitrate ions - Dinker, Manish K.; Ajithkumar, Thalasseril G.; Kulkarni, Prashant S. (ACS Sustainable Chemistry & Engineering, 2017)
A novel bifunctional mesoporous organosilica, PEG-functionalized bis-prolinium chloride bridged mesoporous organosilica (BPBMO) was synthesized by reacting the precursor, PEG-functionalized bis-prolinium chloride bridged organosilane (BPRIL) with tetraethyl orthosilicate (TEOS) in the presence of surfactant. The chemical conformation of BPBMO was investigated by using Fourier transform infrared (FTIR), thermogravimentric analysis (TGA), C-13, and Si-29 cross-polarization/magic angle spinning (CP/MAS) NMR techniques. The characterization represents PEG-linked-prolinium (-N+Cl-) and carboxyl (-COOH) entities, constructing the dicationic framework through siloxane (Si-O-Si) linkages. The pore-wall distribution and the periodicity of BPBMO retained during the synthesis were examined by small-angle X-ray scattering (SAXS), Brunauer-Emmett-TellerBarrett-Joyner-Halenda (BET-BJH), and transmission electron microscopy (TEM) techniques. The results revealed BPBMO as a spherical shaped solid (50-100 nm) having mesopore channels hexagonally arranged with interparticle porosity (S-BET = 487 m(2)/g and D-BJH = 5.1 nm). The material has provided active binding sites for the simultaneous removal of NO3- and Pb2+ ions when introduced in the aqueous solutions of Pb(NO3)(2) (50 mg/L, pH 6). The removal of NO3- by ion-exchange with prolinium (-N+Cl-) entities and the electrostatic interaction of Pb2+ with carboxylate (-COO-) group were characterized by using Raman spectroscopy, ion chromatography, and X-ray photoelectron spectroscopy (XPS) technique. The maximum removal of NO3- and Pia' ions were achieved within 1 h of the adsorption reaction. The adsorption has followed the Langmuir isotherm model with the adsorption capacities (q(m)) of 23.04 and 21.92 mg/g for NO3- and Pb2+ ions, respectively. The efficiency of the adsorbent was also compared with other adsorbents. Further, the BPBMO material has depicted three consecutive adsorption/desorption cycles with negligible loss in the structural conformation.

Lead-free solid state mechanochemical synthesis of Cs2NaBi1-XFeXCl6 double perovskite: reduces band gap and enhances optical properties - Udavant, Rohini; Thawarkar, Sachin; Rondiya, Sachin; Shelke, Ankita; Aher, Rahul; Ajithkumar, Thalasseril G.; Cross, Russell W.; Dzade, Nelson Y.; Jadkar, Sandesh (Inorganic Chemistry, 2023)
Efficient and stable lead-free halide double perovskites (DPs) have attracted great attention for the future generation of electronic devices. Herein, we have developed a doping approach to incorporate Fe3+ ions into the Cs2NaBiCl6 crystal unit and reveal a crystallographic and optoelectronic study of the Cs2NaBi1-xFexCl6 double perovskite. We report a simple solid-state mechanochemical method that has a solvent-free, one-step, green chemistry approach for the synthesis of Cs2NaBi1-xFexCl6 phosphor. The analysis of powder X-ray diffraction (XRD) data determines the contraction of the lattice due to the incorporation of Fe3+ cations, and this effect is well supported by X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM), Raman spectroscopy, and solid-state nuclear magnetic resonance spectroscopy (ss-NMR). The band gap is reduced with increasing Fe content owing to the strong overlap of the Fe-3d orbitals with Cl-3p orbitals and shift of the valence band maxima (VBM) toward higher energies, as confirmed by ultraviolet photoelectron spectroscopy (UPS) and density functional theory (DFT) analyses. Photoluminescence (PL) studies of Cs2NaBi1-xFexCl6 phosphors exhibit a large Stokes shift, broadband emission, and increased PL intensity more than ten times for 15% of Fe content phosphor with enhancement in the average decay lifetimes (up to 38 ns) compared to pristine Cs2NaBiCl6 DP. These results indicate that the transition of dark self-trapping of excitons (STEs) into bright STEs enhances yellow emission. XRD, UV, and thermo-gravimetric analysis (TGA) confirmed that the Cs2NaB1-xFexCl6 DPs have good structural and thermal stabilities. Our findings indicate that the doping of Fe3+ cations into the Cs2NaBiCl6 lattice is a constructive strategy to enhance significantly the optoelectronic properties of these phosphors.